Multicenter Study of Method-Dependent Epidemiological Cutoff Values for Detection of Resistance in Candida spp. and Aspergillus spp. to Amphotericin B and Echinocandins for the Etest Agar Diffusion Method - Espinel Ingroff, A.; Arendrup, M.; Cantón, E.; Córdoba, S.; Dannaoui, E.; García Rodríguez, Juan; González González, Gloria María; Govender, N. P.; Martín Mazuelos, E.; Lackner, Michaela; Lass Flörl, Cornelia; Linares Sicilia, M. J.; et al. (American Society for Microbiology, 2016)
BSTRACT Method-dependent Etest epidemiological cutoff values (ECVs) are not available for susceptibility testing of either Candida or Aspergillus species with amphotericin B or echinocandins. In addition, reference caspofungin MICs for Candida spp. are unreliable. Candida and Aspergillus species wild-type (WT) Etest MIC distributions (microorganisms in a species-drug combination with no detectable phenotypic resistance) were established for 4,341 Candida albicans, 113 C. dubliniensis, 1,683 C. glabrata species complex (SC), 709 C. krusei, 767 C. parapsilosis SC, 796 C. tropicalis, 1,637 Aspergillus fumigatus SC, 238 A. ﬂavus SC, 321 A. niger SC, and 247 A. terreus SC isolates. Etest MICs from 15 laboratories (in Argentina, Europe, Mexico, South Africa, and the United States) were pooled to establish Etest ECVs. Anidulafungin, caspofungin, micafungin, and amphotericin B ECVs (in micrograms per milliliter) encompassing 97.5% of the statistically modeled population were 0.016, 0.5, 0.03, and 1 for C. albicans; 0.03, 1, 0.03, and 2 for C. glabrata SC; 0.06, 1, 0.25, and 4 for C. krusei; 8, 4, 2, and 2 forC. parapsilosis SC; and 0.03, 1, 0.12, and 2 for C. tropicalis. The amphotericin B ECV was 0.25 g/ml for C. dubliniensis and 2, 8, 2, and 16 g/ml for the complexes of A. fumigatus, A. ﬂavus, A. niger, and A. terreus, respectively. While anidulafung in Etest ECVs classiﬁed 92% of the Candida fks mutants evaluated as non-WT, the performance was lower for caspofungin (75%) and micafungin (84%) cutoffs. Finally, although anidulafungin (as an echinocandin surrogate susceptibility marker) and amphotericin B ECVs should identify Candida and Aspergillus isolates with reduced susceptibility to these agents using the Etest, these ECVs will not categorize a fungal isolate as susceptible or resistant, as breakpoints do. KEYWORDS ECVs, Etest ECVs, Etest MICs Candida, Etest MICs Aspergillus, WT isolates, amphotericin B resistance, antifungal resistance, echinocandin resistance, non-WT, susceptibility marker